Implementing Scalable DevOps Pipelines for Machine Learning Model Monitoring and Performance Management (Journal of Artificial Intelligence & Research, 2024)
The integration of machine learning (ML) models into production environments has introduced significant challenges related to performance monitoring, model drift, and retraining needs. As organizations strive to maintain competitive advantages through data-driven insights, the implementation of scalable DevOps pipelines becomes paramount. This paper explores techniques for establishing robust DevOps pipelines that facilitate continuous monitoring of ML model performance. By employing strategies such as automated monitoring tools, feedback loops, and retraining mechanisms, organizations can proactively manage model degradation and adapt to changing data distributions. This discussion aims to equip practitioners with practical methodologies for implementing scalable DevOps pipelines that ensure sustained model accuracy and reliability in dynamic production settings.